Overcoming resistance to BRAF inhibitors - Arozarena, Imanol (Ann Transl Med, 2017)
The discovery of activating mutations in the serine/threonine (S/T) kinase BRAF followed by a wave of follow-up research manifested that the MAPK-pathway plays a critical role in melanoma initiation and progression. BRAF and MEK inhibitors produce an unparalleled response rate in melanoma, but it is now clear that most responses are transient, and while some patients show long lasting responses the majority progress within 1 year. In accordance with the key role played by the MAPK-pathway in BRAF mutant melanomas, disease progression is mostly due to the appearance of drug-resistance mechanisms leading to restoration of MAPK-pathway activity. In the present article we will review the development, application and clinical effects of BRAF and MEK inhibitors both, as single agent and in combination in the context of targeted therapy in melanoma. We will then describe the most prominent mechanisms of resistance found in patients progressed on these targeted therapies. Finally we will discuss strategies for further optimizing the use of MAPK inhibitors and will describe the potential of alternative combination therapies to either delay the onset of resistance to MAPK inhibitors or directly target specific mechanisms of resistance to BRAF/MEK inhibitors.